Holocene palaeoclimate and sea level fluctuation recorded from the coastal Barker Swamp, Rottnest Island, south-western Western Australia - Gouramanis, Chris. (2013)
The Holocene palaeoclimatic history of south-western Western Australia (SWWA) has received little attention compared to south-eastern Australia, and this has resulted in conflicting views over the impact of climate variability in the region. We present here a well-dated, high-resolution record from two overlapping sediment cores obtained from the centre of Barker Swamp, Rottnest Island, offshore Perth. The records span the last 8.7 ka, with the main lacustrine phase occurring after 7.4 ka. This site preserves both pollen and several ostracod taxa. The pollen record suggests a long-term shift from the early-mid Holocene to the late Holocene to drier conditions with less shrubland and more low-ground cover and less fire activity. A salinity transfer function was developed from ostracod faunal assemblage data and trace metal ratios (Mg/Ca, Sr/Ca and Na/Ca) and stable isotopes (δ18O and δ13C) analysed on selected ostracod valves. These provide a detailed history of evaporation/precipitation (E/P) differences that clearly shows that the SWWA region was subjected to significant climatic shifts over the last 7.4 ka, with a broad shift towards increased aridity after 5 ka. The swamp ranged from fresh to saline as recorded in the ostracod valve chemistry and the independently-derived salinity transfer function. The ostracod record also indicates that a sea-level highstand occurred between ca. 4.5 and 4.3 ka, with probable step-wise increases at 6.75, 6.2, and 5.6 ka, with the last vestiges of salt water intrusion at ca. 1 ka. After about 2.3 ka, the fresh, groundwater lens that underlies the western portion of the island intersected the swamp depression, influencing the hydrology of the swamp. The broad climatic changes recorded in Barker Swamp are also compared with data from southern South Africa, and it is suggested that the Southern Annular Mode appears to have been the dominant driver in the climate of these regions and that the Indian Ocean Dipole is of little importance in the southern regions of the south-western Cape of Africa and south-western Western Australia.